Compressibility of dense nuclear matter in the ρ-meson variant of the Skyrme model - Miguel Huidobro; Paul Leask; Carlos Naya; Andrzej Wereszczyński (Journal of High Energy Physics, 2025)
Abstract We show that coupling the SU(2)-valued Skyrme field to the ρ-meson solves the long-standing issue of (in)compressibility in the solitonic Skyrme model. Even by including only one ρπ interaction term, motivated by a holographic-like reduction of Yang-Mills action by Sutcliffe, reduces the compression modulus from K 0 ≃ 1080 MeV, in the massive Skyrme model, to K 0 ≃ 351 MeV.